2007
DOI: 10.1002/eji.200636705
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the lethal synergism between Trypanosoma cruzi infection and LPS: A role for increased macrophage reactivity

Abstract: Various infections sensitize to lethal shock by promoting hyperactivation of macrophages to LPS stimulation. Although macrophages are thought to be deactivated upon contact with apoptotic cells during Trypanosoma cruzi infection, T. cruzi infection also sensitizes mice to endotoxemia. Herein, we studied the mechanisms of sensitization to endotoxemia in T. cruzi-infected mice in order to solve the paradox. Live (but not fixed) trypomastigotes from various stocks sensitized mice to endotoxemia. Mice deficient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Moreover, evidence suggests that administration of NSAIDs may enhance mortality in chagasic patients [12]. Conversely, others have found that inhibition of PG synthesis/release reduces parasitemia and extends survival of mice infected with T. cruzi [1417]. This was often associated with a decrease in the levels of circulating inflammatory cytokines (such as TNF- α , IFN- γ , and IL-10) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evidence suggests that administration of NSAIDs may enhance mortality in chagasic patients [12]. Conversely, others have found that inhibition of PG synthesis/release reduces parasitemia and extends survival of mice infected with T. cruzi [1417]. This was often associated with a decrease in the levels of circulating inflammatory cytokines (such as TNF- α , IFN- γ , and IL-10) [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the present work suggests that GIF is one of the emerging immunoregulatory cytokines. Although the unmodified GIF has been implicated in the activation of innate immunity (10), the sensitivity of GIFdeficient mice to endotoxin shock has been controversial (11,12,14). Our in vitro experiments indicated that expression of GIF is not required for macrophages or dendritic cells to respond to TLR ligands.…”
Section: Discussionmentioning
confidence: 70%
“…The initial report of the mutant mice demonstrated a reduced rate of endotoxin shock (11). However, the same (14) and other (12) lines of the mutant mice later showed a normal sensitivity to LPS. Thus, the role of GIF in innate immunity needs to be reevaluated.…”
mentioning
confidence: 93%
“…Therefore, increased apoptosis during infection might help parasite persistence, by affecting macrophagemediated immunity [16]. Nonetheless, there is evidence of macrophage activation and control of parasite infection in different experimental models of Chagas' disease [21,22].…”
Section: Apoptotic Cells and Macrophagesmentioning
confidence: 99%